Protective effects of antioxidants against cadmium-induced oxidative damage in rat testes - Kara, Haki; Cevik, Aydin; Konar, Vahit; Dayangac, Alpaslan; Yilmaz, Mahmut (Humana Press Inc, 2007)
The protective effects of melatonin, vitamin E, and selenium alone or in combination were tested against cadmium-induced oxidative damage in rat testes. A total of 60 male rats were equally divided into five study groups, one of which acted as control receiving subcutaneous injections of physiological saline. The remaining four groups were treated with subcutaneous injections of cadmium chloride at a dose of 1 mg/kg weight. The first study group received no treatment. The second group was treated with a combination of 60 mg/kg vitamin E and 1 mg/kg sodium selenite. Group 3 was treated with 10 mg/kg melatonin, and the fourth group received a combination of vitamin E, sodium selenite, and melatonin at the doses mentioned above. After 1 month, the animals were killed, and the testes were excised for histological inspection and determination of tissue malondialdehyde and the activity of superoxide dismutase. The animals receiving no treatment showed significantly higher malondialdehyde levels and reduced activity of the enzyme (p < 0.05). Treatment with antioxidants resulted in a significant reduction in malondialdehyde when compared to the nontreated animals (p < 0.05) and an increase in the superoxide dismutase activity that was almost the same as the controls. The combination of melatonin, vitamin E, and selenium appears to have the more profound effect against cadmium-induced testicular injury.
Keywords: cadmium; vitamin E; selenium; melatonin; oxidative damage; rat testes